The Impact of the E-Sport Curriculum Toward Online Game Addiction - Mumtaz, Emka Farah; Ragamustari, Safendrri Komara; Hirawan, Fajar Bambang (TAZKIYA Journal of Psychology, 2021)
Increasing cases of gamers in Indonesia reaching 34 million and addicted users to games have an impact on physical and psychological conditions. These phenomena need suitable intervention and government concern. Many alternatives can be an option. This study aims to identify the influence of E-sport Curriculum Policy toward Game Addiction among adolescents. This research uses a mixed-method in which the quantitative analysis uses regression data analyses in 4-scale of Likert and qualitative uses interview. The key question is based on Leman’s measurement criteria in gaming addiction, Custer and Russel’s E-sport Curriculum through feasibility test in the form of reliability test and validity test. The sample of this study are adolescents including junior and senior high school students with purposive random sampling. The hypothesis result shows the value of R-Square is 0.509 meaning that the proportion of variants of the game addiction behavior described by all independent variables is 50.9%, while 49.1% is influenced by other variables not examined. The combination of cognitive and behavioral aspects of the e-sports curriculum is believed to be a solution. The knowledge provided is in line with the treatment of game addiction players, and what is done will cause a reflection effect in line with the experts’ point of view.